Physical Literacy, Mental Health, and Quality of Life: Analysis of Sports Students Based on Gender Differences - Marisa Noviyanti Fajrah Ilsya; Salman; Derry Renanda Putra Siahaan; Ivan Rivan Firdaus; Nadila Maesara (Universitas Negeri Semarang, 2025)
Introduction: Physical literacy is crucial for the mental health and quality of life of university sports students, yet a research gap exists in understanding how these constructs interact through a gender-sensitive lens, particularly within sports education programs where psychological distress is rising despite high physical competence. Objectives: This study aims to analyze the relationship between physical literacy, mental health, and quality of life among sports students, considering the role of gender as a covariate. The research design used is quantitative with a descriptive correlational approach. Method: The research sample consisted of 211 students from the Faculty of Sports and Health Education, Indonesia University of Education. The instruments used included the Perceived Physical Literacy Instrument (PPLI), Short Mental Health Scale (SKM-12), and WHOQOL-BREF. Data analysis was performed using descriptive statistics, classical assumption tests, multiple regression, and ANCOVA. Result: The results show that the average scores for physical literacy, mental health, and quality of life are in the moderate to high range with a normal and homogeneous data distribution. Multiple regression analysis shows that mental health has a significant effect on quality of life (B = 1.217; p < 0.001), while physical literacy has no significant effect (B = 0.171; p = 0.072). Simultaneously, both variables were able to explain 52.6% of the variation in students' quality of life (R² = 0.526; p < 0.001). ANCOVA analysis confirmed that the effect of mental health remained significant after controlling for gender, while physical literacy and gender differences were not significant. Conclusion: These findings indicate that mental health is the primary predictor of student athletes' quality of life, while physical literacy plays a more supportive role. Intervention recommendations focus on strengthening mental health integrated with improving physical literacy to comprehensively support student athletes' well-being.